Crocetin and related oxygen diffusion‐enhancing compounds: Review of chemical synthesis, pharmacology, clinical development, and novel therapeutic applications - Shah, Hriday M.; Jain, Ashvi S.; Joshi, Shreerang V.; Kharkar, Prashant S. (Drug development research, 2021)
The current pandemic forced us to introspect and revisit our armamentarium of medicinal agents which could be life‐saving in emergency situations. Oxygen diffusion‐enhancing compounds represent one such class of potential therapeutic agents, particularly in ischemic conditions. As rewarding as the name suggests, these agents, represented by the most advanced and first‐in‐class molecule, trans‐sodium crocetinate (TSC), are the subject of intense clinical investigation, including Phase 1b/2b clinical trials for COVID‐19. Being a successor of a natural product, crocetin, TSC is being investigated for various cancers as a radiosensitizer owing to its oxygen diffusion enhancement capability. The unique properties of TSC make it a promising therapeutic agent for various ailments such as hemorrhagic shock, stroke, heart attack, among others. The present review outlines various (bio)synthetic strategies, pharmacological aspects, clinical overview and potential therapeutic benefits of crocetin and related compounds including TSC. The recent literature focusing on the delivery aspects of these compounds is covered as well to paint the complete picture to the curious reader. Given the potential TSC holds as a first‐in‐class agent, small‐ and/or macromolecular therapeutics based on the core concept of improved oxygen diffusion from blood to the surrounding tissues where it is needed the most, will be developed in future and satisfy the unmet medical need for many diseases and disorders.